Assessing the Effectiveness of SMEs Loans in Mahendranagar: Utilization, Misuse, and Growth Barriers - Bhatt, Santosh Raj (The Management Review, 2025)
Small and Medium Enterprises (SMEs) are the backbone of local economies, especially in emerging regions like Mahendranagar, Nepal. Despite the availability of various loan products from financial institutions, their effectiveness in supporting business growth remains inconsistent. This study investigates the role of loan products in enhancing SME performance, identifies challenges in loan utilization, and explores key issues such as financial literacy, misuse of loans, and loan monitoring gaps. Data were collected through field surveys, interviews with business owners, and analysis of bank reports. Findings highlight the need for improved financial education, stricter loan monitoring, and customized loan products. Recommendations include better financial literacy programs, stronger monitoring systems, and tailored banking services to address the unique needs of SMEs.